(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
Accreditation processes have been considered, for the careers that had experienced it, as rigorous, demanding and even exhausting processes; this article shares the experience of a University Academic School that opted not only for the accreditation of one career but of two and together; with innovation on the way of doing accreditation, not changing the models or guides but showing that the accreditation by clusters has more advantages for the university and for the participants. This is the systematization of the living experience at a State University in Costa Rica that has been committed to accreditation, as well as to improvement processes and the quest for permanent quality.